Pharmacological inhibition of receptor protein tyrosine phosphatase β/ζ decreases Aβ plaques and neuroinflammation in the hippocampus of APP/PS1 mice - Fontán-Baselga, Teresa; Cañeque-Rufo, Héctor; Rivera-Illades, Elisa; Gramage, Esther; Zapico, José María; de Pascual-Teresa, Beatriz; Ramos-Álvarez, María Del Pilar; Herradón, Gonzalo; Vicente-Rodríguez, Marta (Frontiers in Pharmacology, 2024)
Alzheimer's disease (AD) is a major neurodegenerative disorder that courses with chronic neuroinflammation. Pleiotrophin (PTN) is an endogenous inhibitor of Receptor Protein Tyrosine Phosphatase (RPTP) β/ζ which is upregulated in different neuroinflammatory disorders of diverse origin, including AD. To investigate the role of RPTPβ/ζ in neuroinflammation and neurodegeneration, we used eight-to ten-month-old APP/PS1 AD model. They were administered intragastrically with MY10, an inhibitor of RPTPβ/ζ, at different doses (60 and 90 mg/kg) every day for 14 days. Treatment with 90 mg/kg MY10 significantly reduced the number and size of amyloid beta (Aβ) plaques in the dorsal subiculum of the hippocampus of APP/PS1 mice. In addition, we observed a significant decrease in the number and size of astrocytes in both sexes and in the number of microglial cells in a sex-dependent manner. This suggests that RPTPβ/ζ plays an important role in modulating Aβ plaque formation and influences glial responses, which may contribute to improved Aβ clearance. In addition, MY10 treatment decreased the interaction of glial cells with Aβ plaques in the hippocampus of APP/PS1 mice. Furthermore, the analysis of proinflammatory markers in the hippocampus revealed that MY10 treatment decreased the mRNA levels of Tnfa and Hmgb1. Notably, treatment with MY10 increased Bace1 mRNA expression, which could be involved in enhancing Aβ degradation, and it decreased Mmp9 levels, which might reflect changes in the neuroinflammatory environment and impact Aβ plaque dynamics. These results support the therapeutic potential of inhibition of RPTPβ/ζ in modulating Aβ pathology and neuroinflammation in AD.